Eudragit S100 Entrapped Liposome for Curcumin Delivery: Anti-Oxidative Effect in Caco-2 Cells - Vincenzo De Leo (Coatings, 2020)
Curcumin is a natural polyphenol with strong antioxidant activity. However, this molecule shows a very poor bioavailability, instability, and rapid metabolism in vivo. In this work curcumin was loaded in Eudragit-coated liposomes to create a gastroresistant carrier, able to protect its load from degradation and free it at the site of absorption in the colon region. Small unilamellar vesicles were prepared and coated with Eudragit by a pH-driven method. The physico-chemical properties of the prepared systems were assessed by light scattering, transmission electron microscopy, infrared spectroscopy, and differential scanning calorimetry. The uptake of vesicles by Caco-2 cells and the anti-oxidant activity in cells were evaluated. The produced vesicles showed dimensions of about forty nanometers that after covering with Eudragit resulted to have micrometric dimensions at acid pH. The experiments showed that at pH > 7.0 the polymeric coating dissolves, releasing the nanometric liposomes and allowing them to enter Caco-2 cells. Delivered curcumin loaded vesicles were then able to decrease significantly ROS levels as induced by H2O2 in Caco-2 cells. The proposed work showed the possibility of realizing effective gastroresistant curcumin liposome formulations for the delivery of antioxidant molecules to Caco-2 cells, potentially applicable to the treatment of pathological conditions related to intestinal oxidative stress.